Consórcio público regional de resíduos sólidos do Seridó/RN: perspectivas de um novo modelo de gestão - Silva, Wagner Luiz Alves da (2015)
The problem of solid waste that involves the management, the management and the allocation of these is an issue that permeates all spheres of society, which denotes environmental implications that contribute to the discussion of the environmental crisis in progress. From this perspective, this study aims to investigate and understand the role that consortia, especially the Regional Public Waste Consortium Solid Seridó/RN have waste management, in order to observe their strengths and weaknesses in order to conclude whether they are an appropriate solution to the problem of solid waste. In studying a region that is undergoing a process of institutional organization guided in the solid waste, the focus turned into an interesting academic research point. Since this is a qualitative research, readings were taken of relevant authors to the object and the following legal frameworks, namely: the National Basic Sanitation Policy (Law nº 11.445/2007), the National Policy on Solid Waste (Law nº 12.305/2010 ) and the Law on Public Consortia (Law nº 11.107/2005). The consortium region has about 290.000 inhabitants, generated 40.000 tons of waste a year. As for the final disposal of waste, all municipalities in the region deposit their waste in the open, or in garbage dumps. In the analysis of the Consortium Seridó, a list of issues that are hindering their implementation has been identified. The demands come mainly from the political sphere, but also financial, technical and logistical. It is expected that with the realization of the Consortium by building its supporting structures (overfill Station and Landfill), a new model of solid waste management is implemented.